INTEGRASI MITIGASI BENCANA DALAM PERENCANAAN PERKOTAAN UNTUK PEMBANGUNAN TANGGUH DI KOTA SABANG - Akmal, Muhammad Nur; Sunarty, Risma; Mubarrak, Dzakiyul (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2025)
This study explores public perceptions regarding the integration of disaster mitigation into urban planning in Sabang, a coastal city in Indonesia highly vulnerable to natural hazards such as tsunamis and earthquakes. Employing a structured survey administered to 26 stakeholders including local officials, community leaders, and tourists. The research identifies strong consensus on the importance of embedding disaster risk reduction (DRR) into development strategies. Findings show that all respondents agreed, with 80.8% strongly agreeing, that disaster mitigation should be a key component of Sabang’s planning processes. The most critical elements identified were development location, urban spatial planning, support infrastructure, building design, and regulatory frameworks. Despite this broad support, only 38.5% of participants believed that current tourism management adequately incorporates disaster risk analysis, revealing a significant gap between perceived necessity and actual implementation. These results highlight the need for coordinated, cross-sectoral planning efforts that align policy with public expectations. The study contributes to resilience discourse by emphasizing the role of stakeholder perspectives in advancing inclusive, risk informed urban development in disaster-prone tourist destinations.